2017
DOI: 10.1038/s41598-017-11366-y
|View full text |Cite
|
Sign up to set email alerts
|

MITF and BRN2 contribute to metastatic growth after dissemination of melanoma

Abstract: Melanoma tumors are highly heterogeneous, comprising of different cell types that vary in their potential for growth and invasion. Heterogeneous expression of the Microphthalmia-associated Transcription Factor (MITF) and the POU domain transcription factor BRN2 (POU3F2) has been found in malignant melanoma. Changing expression of these transcription factors as the disease progresses has been linked to the metastatic mechanism of phenotype switching. We therefore investigated the effects of MITF and BRN2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 41 publications
2
51
0
1
Order By: Relevance
“…Using RNAi we confirmed previous findings (Cook et al, 2005;Simmons et al, 2017;Smith et al, 2016;Thurber et al, 2011;Wellbrock et al, 2008) that both, BRN2 and PAX3 contribute to Figure S3). BRN2 expression is induced by MAPK signalling and is used by BRAF V600E to stimulate MITF expression (Kundu et al, 2017;Wellbrock et al, 2008).…”
Section: Pax3 Is Required For Braf V600e Mediated Mitf Expressionsupporting
confidence: 90%
See 2 more Smart Citations
“…Using RNAi we confirmed previous findings (Cook et al, 2005;Simmons et al, 2017;Smith et al, 2016;Thurber et al, 2011;Wellbrock et al, 2008) that both, BRN2 and PAX3 contribute to Figure S3). BRN2 expression is induced by MAPK signalling and is used by BRAF V600E to stimulate MITF expression (Kundu et al, 2017;Wellbrock et al, 2008).…”
Section: Pax3 Is Required For Braf V600e Mediated Mitf Expressionsupporting
confidence: 90%
“…In PAX3 low /BRN2 high A375 cells BRN2 is the main driver of MITF expression, and increasing BRN2 enhances this activity, but in PAX3 high /BRN2 low 501mel cells overexpressed BRN2 can switch the PAX3‐driven transcription to the weaker BRN2/PAX3 driven transcription. The rheostat can also explain why depletion of endogenous BRN2 from different melanoma cell lines can result in different degrees of MITF reduction (Cook et al, ; Kundu et al, ; Simmons et al, ; Thurber et al, ; Wellbrock et al, ) or even an increase in MITF expression, as reported in 501mel cells (Goodall et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, our study for the first time suggests that melanomas harbor exceptionally wide H3K4me3 domains on key drivers of invasion and metastasis ( POU3F2 48,43 , SOX9 49 , PDGFRA 50 and PDGFA) and this transition was associated with increased transcriptional activation. It is likely, barring physical and chemical barrier, that addition of H3K4me3 marks on adjacent nucleosome may require less energy due to already recruited methylation machinery, and hence may be a preferred mode for relative increase in gene expression to meet the needs of metastatic cells.…”
Section: Discussionmentioning
confidence: 70%
“…The level of MITF is very important for melanoma, since medium levels of MITF expression were found in melanoma patients with high mortality (Agnarsdóttir et al 2012), a low activity is related to stem cell-like or invasive potential, while high levels regulate either differentiation or proliferation (Carreira et al 2006;Hartman and Czyz 2015). Importantly, decrease of MITF levels is frequently observed in different melanoma cells (Fane et al 2017;Simmons et al 2017;Vlčková et al 2018), while the depletion of MITF significantly reduced the migration of melanoma cells . Noteworthy, all the results suggest that the role of MITF in melanoma cell migration depends on the used cell line.…”
Section: Discussionmentioning
confidence: 99%